What were the spatial-temporal distributions of agricultural water resource efficiency in China? - Wang, Jianfang; Sheng, Hongxia; Yang, Guangming; Li, Darong; Qin, Yizhi; Zhou, Changchun; Zou, Lijuan (Frontiers in Environmental Science, 2025)
Improving the utilization efficiency of agricultural water resources constitutes one of the effective approaches to addressing the current issue of water resource scarcity. This study, from the perspective of water resource pollution severity, integrates the DPSIRM model with the Slacks-Based Measure (SBM) method, thereby constructing a novel DPSIRM-SBM model to measure and analyze the agricultural water resource utilization efficiency across 31 provinces in China. Furthermore, it employs Moran’s Index and standard deviational ellipse analysis to investigate the spatiotemporal distribution patterns. The findings are as follows: (1) From 2007 to 2021, the agricultural water resource utilization efficiency in China generally maintained a stable development trend, fluctuating around 0.8; (2) The spatiotemporal distribution of agricultural water resource utilization efficiency among provinces and municipalities exhibited non-agglomerative and imbalanced characteristics, with significant spatial disparities and weak interregional radiation effects; (3) From a spatial distribution standpoint, the agricultural gray water footprint demonstrated a pattern of “high in the west and low in the east,” accompanied by agglomeration effects; (4) From a regional perspective, the eastern region outperformed the central and western regions, with the central region exhibiting pronounced efficiency fluctuations and the western region persistently displaying low efficiency. The study’s results suggest that enhancing the agricultural water resource utilization efficiency in China necessitates intensifying efforts in water pollution control, breaking path dependencies through interregional ecological compensation, and strengthening the optimizing role of market-based mechanisms in resource allocation.